A method for preparing brominated polystyrene
By supporting the carrier as the main chain bromination inhibitor, the color performance and thermal stability problems caused by bromine radicals were solved during the preparation of bromine polystyrene, and the efficient and low-cost preparation of bromine polystyrene was achieved.
Patent Information
- Application Number
- CN202510104239.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-23
AI Technical Summary
In the existing brominated polystyrene preparation methods, the direct bromination method causes the bromination agent to generate bromine radicals, resulting in free radical substitution of the polystyrene main chain hydrogen, affecting color performance and thermal stability; the synthesis route of bromination first and then polymerization method is long and the process is complex, resulting in increased costs and extended production cycles.
The support is supported titanium tetrachloride as the main chain bromination inhibitor, and the bromination reaction is carried out under the catalysis of the primary bromination catalyst. By controlling the reaction conditions and the amount of additives, the free radical substitution phenomenon is reduced, and the color performance and thermal stability of brominated polystyrene are improved.
The high bromine content, narrow molecular weight distribution, good color performance and thermal stability of brominated polystyrene are achieved, which simplifies the process flow, shortens the reaction time, and reduces production costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of brominated polystyrene preparation, and in particular to a method for preparing brominated polystyrene. Background Art
[0002] Brominated polystyrene is a brominated organic flame retardant with excellent flame retardancy, thermal stability and light stability, as well as excellent physical and mechanical properties. It is widely used in engineering plastics such as polyhexamethylene adipamide, polybutylene terephthalate, polyethylene terephthalate and polyphenylene ether.
[0003] Preparation methods for brominated polystyrene include direct bromination method and bromination first followed by polymerization method. In the direct bromination method, a bromination agent is directly used to brominate polystyrene to obtain brominated polystyrene. In the bromination first followed by polymerization method, a bromination agent is used to brominate styrene to obtain a bromine-containing monomer, which is then polymerized to obtain brominated polystyrene. The direct bromination method has a short synthesis route, a simple synthesis process, and low requirements for production equipment. When a bromination agent is used to brominate polystyrene, the bromination agent generates bromine free radicals, which can undergo electrophilic substitution with multiple hydrogens on the benzene ring of polystyrene, thereby ensuring that the prepared brominated polystyrene has a high bromine content. However, when the bromine free radical undergoes electrophilic substitution, while undergoing electrophilic substitution with hydrogens on the benzene ring, it will also undergo free radical substitution with a small amount of hydrogens on the main chain of the polystyrene. Since the bromine on the main chain of the polystyrene has a great influence on the color of the brominated polystyrene, the color of the prepared brominated polystyrene will be affected. Yellowing, color performance is reduced, and due to the low bond energy between the carbon and bromine on the polystyrene main chain, the prepared brominated polystyrene will decompose when heated to about 200°C, further resulting in poor thermal stability of the prepared brominated polystyrene. Compared with the direct bromination method, the bromination-polymerization method has a high yield, and the prepared brominated polystyrene does not contain bromine on the main chain. Therefore, the color of the prepared brominated polystyrene is close to white and has good thermal stability. However, the bromination-polymerization method has a long synthesis route, a complex synthesis process, and high requirements for production equipment, which increases the cost of brominated polystyrene and extends the production cycle.
[0004] After studying the problems existing in the direct bromination method, it was found that the reason why bromine free radicals replace hydrogen on a small amount of the main chain of polystyrene with free radicals is that the existing direct bromination method generally uses an organic solvent to dissolve polystyrene, then adds phosphorus trichloride as a dehydrating agent, adds aluminum chloride as a catalyst, and then uses bromine as a brominating agent to brominate and prepare brominated polystyrene. Among them, the catalyst aluminum chloride is a Lewis acid, which contains an unoccupied p orbital in the molecule and can accept an electron pair. It is a strong electrophilic reagent. When catalyzing, the catalyst aluminum chloride can form a complex with the π electron system of the benzene ring in polystyrene, so that the electron density on the benzene ring in polystyrene is reduced, making it easier to be attacked by electrophilic reagents. However, after the catalyst aluminum chloride is complexed with polystyrene, it will also cause hydrogen on the main chain of polystyrene to be more easily replaced by free radicals. To address this problem, the most commonly used method is to add titanium tetrachloride as a main chain bromination inhibitor, thereby improving the color performance and thermal stability of the prepared brominated polystyrene.
[0005] However, after adding titanium tetrachloride as a main chain bromination inhibitor, the following problems still exist: first, the main chain bromination inhibitor titanium tetrachloride is a Lewis acid and can also form a complex with polystyrene through a strong interaction with the benzene ring in polystyrene to promote the reaction. It is a low-activity catalyst. After the catalyst aluminum trichloride and the main chain bromination inhibitor titanium tetrachloride are directly mixed and added, the reaction may cause rapid heat release, causing the main chain of polystyrene with a relatively small molecular weight to break, affecting the free radical substitution of hydrogen on the benzene ring in polystyrene, and further affecting the molecular weight distribution, bromine content and thermal stability of the prepared brominated polystyrene; second, the main chain bromination inhibitor titanium tetrachloride is sensitive to air and water and is easily ineffective in the reaction, resulting in a weakened inhibitory effect on the bromination of the main chain in the later stage of the reaction, which further leads to reduced color properties and thermal stability of the prepared brominated polystyrene.
[0006] In view of the above problems, the inventors solve the problems by the following method: after using a carrier to load titanium tetrachloride, a main chain bromination inhibitor, as a primary bromination catalyst, under the catalysis of the primary bromination catalyst, bromine is added dropwise to perform a primary bromination reaction on polystyrene, so that free radical substitution of some hydrogen on the benzene ring in polystyrene can be performed while protecting the main chain, and then the catalyst aluminum chloride is added, and bromine is added dropwise to perform a secondary bromination reaction on polystyrene to prepare brominated polystyrene, wherein the polystyrene used is a special polystyrene with a narrow molecular weight distribution, and the amount of the primary bromination catalyst, the catalyst aluminum chloride, and the bromine is controlled respectively in the bromination reaction, so as to control the heat release of the reaction. When the above method is used for pilot testing, brominated polystyrene with a narrow molecular weight distribution, good color performance and thermal stability can be obtained, but the following problems still exist: first, two feedings are required, and there are problems of poor reaction controllability and long reaction time; second, titanium tetrachloride is easily hydrolyzed during the loading process, and the loading amount is small, and the release rate after loading is slow, so there is still a problem of poor main chain bromination inhibition effect. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention provides a method for preparing brominated polystyrene. The prepared brominated polystyrene has good color performance and thermal stability, high bromine content, narrow molecular weight distribution, good reaction controllability and short reaction time.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing brominated polystyrene, comprising: preparing a main chain bromination inhibitor, preparing a catalyst, and reacting;
[0010] The method for preparing the main chain bromination inhibitor comprises: preparing a composite carrier, loading;
[0011] The composite carrier is prepared by adding ammonia water, aluminum hydroxide and anhydrous ethanol into a reaction kettle, controlling the temperature of the reaction kettle to 65-70°C, controlling the stirring speed to 200-300 rpm, stirring for 30-40 minutes to obtain a mixed phase; adding polystyrene and toluene into a reaction kettle with a reflux device, controlling the temperature of the reaction kettle to 111-113°C, controlling the stirring speed to 200-300 rpm, stirring and reflux for 20-30 minutes, cooling the temperature to 40-50°C, stopping the reflux, adding tetraethyl orthosilicate, stirring for 20-30 minutes, and obtaining a Organic phase; adding all the above mixed phases to a reactor, controlling the temperature of the reactor to 65-70°C, controlling the stirring speed to 200-300rpm, then adding all the above organic phases to the reactor, adding polyethylene glycol monooctylphenyl ether, continuing to stir for 40-50min, naturally cooling to room temperature, stirring for 10-12h, then adding to a centrifuge, controlling the centrifugal speed of the centrifuge to 4000-5000rpm, centrifuging for 10-12min, taking the precipitate, washing the precipitate with anhydrous ethanol for 3-5 times, and drying to obtain a composite carrier;
[0012] In the preparation of the composite carrier, the usage ratio of ammonia water, aluminum hydroxide, anhydrous ethanol, polystyrene, toluene, tetraethyl orthosilicate, and polyethylene glycol monooctylphenyl ether is 1-1.1L:90-100g:5-6L:2-2.3g:0.44-0.46L:30-32g:65-70g;
[0013] The mass concentration of the ammonia water is 20%;
[0014] The D90 particle size of the aluminum hydroxide is 2 μm;
[0015] The number average molecular weight Mn of the polystyrene is 75,000, and the molecular weight distribution PD is 1.2;
[0016] The loading, adding the composite carrier, titanium tetrachloride and ethylene dichloride into a reactor, continuously introducing nitrogen into the reactor, controlling the stirring speed of the reactor to 200-300 rpm, stirring at room temperature for 50-60 min, filtering, taking the filter residue, and vacuum drying to obtain a main chain bromination inhibitor;
[0017] In the load, the usage ratio of the composite carrier, titanium tetrachloride and ethylene dichloride is 100-110 g: 20-25 g: 1-1.2 L;
[0018] The nitrogen introduction rate is 300-350mL / min;
[0019] The catalyst preparation method comprises the following steps: adding the first portion of water to a reactor, controlling the temperature of the reactor to 40-50° C., controlling the stirring speed to 400-500 rpm, adding a large molecular sodium polyacrylate, stirring for 10-20 min after the addition is completed, adding a small molecular sodium polyacrylate, and continuing to stir for 2-2.5 h after the addition is completed, to obtain a sodium polyacrylate aqueous solution; adding aluminum chloride and the second portion of water to the reactor, controlling the temperature of the reactor to 40-50° C., controlling the stirring speed to 400-500 rpm, stirring for 10-20 min, dripping all of the sodium polyacrylate aqueous solution, continuing to stir for 2-3 h after the dripping is completed, naturally cooling to room temperature, standing for 30-35 h, filtering, taking a filter residue, completely immersing the filter residue in an aluminum chloride aqueous solution, standing for 2-3 h at room temperature, filtering, taking a filter residue, and drying to obtain a catalyst;
[0020] In the preparation of the catalyst, the usage ratio of the first portion of water, macromolecular sodium polyacrylate, small molecule sodium polyacrylate, aluminum chloride, the second portion of water, and aluminum chloride aqueous solution is 14-15L:10-12g:9-10g:1000-1200g:20-23L:0.9-1L;
[0021] The molecular weight of the macromolecular sodium polyacrylate is 3 million;
[0022] The molecular weight of the small molecule sodium polyacrylate is 1 million;
[0023] The mass concentration of the aluminum chloride aqueous solution is 10%;
[0024] The addition rate of the macromolecular sodium polyacrylate is 0.8-1 g / min;
[0025] The addition rate of the small molecule sodium polyacrylate is 0.7-0.8 g / min;
[0026] The dropping time of the sodium polyacrylate aqueous solution is 50-60min;
[0027] The reaction comprises adding polystyrene and ethylene dichloride into a reactor, continuously introducing nitrogen into the reactor for 10-20 minutes, controlling the temperature of the reactor to 35-40° C., controlling the stirring speed to 200-300 rpm, stirring for 30-40 minutes, controlling the temperature of the reactor to 0-2° C., adding a main chain bromination inhibitor and a catalyst, stirring for 20-30 minutes, dropping a dichloroethane solution of N-bromosuccinimide, and after the dropping is completed, controlling the temperature of the reactor to room temperature, stirring for 1.5 hours, terminating the reaction, washing with a sodium hydroxide aqueous solution for 6-7 times, washing with water for 3-4 times, and then filtering, evaporating and crystallizing the filtrate, filtering, and vacuum drying to obtain brominated polystyrene;
[0028] In the reaction, the usage ratio of polystyrene, ethylene dichloride, main chain bromination inhibitor, catalyst, and ethylene dichloride solution of N-bromosuccinimide is 100-110 g: 1.5-1.8 L: 34-35 g: 6-6.2 g: 5.2-5.4 L;
[0029] The ratio of the amount of polystyrene used to the amount of sodium hydroxide aqueous solution used in each washing when washing with sodium hydroxide aqueous solution and the amount of water used in each washing when washing with water is 100-110 g: 0.7-0.8 L: 0.7-0.8 L;
[0030] The number average molecular weight Mn of the polystyrene is 75,000, and the molecular weight distribution PD is 1.2;
[0031] The mass concentration of the dichloroethane solution of N-bromosuccinimide is 10%;
[0032] The mass concentration of the sodium hydroxide aqueous solution is 20%;
[0033] The nitrogen introduction rate is 300-350mL / min;
[0034] The dropwise addition time of the dichloroethane solution of N-bromosuccinimide is 50-60 minutes.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] (1) The method for preparing brominated polystyrene of the present invention comprises preparing a main chain bromination inhibitor, preparing a catalyst and reacting. The preparation of the main chain bromination inhibitor comprises preparing a composite carrier and a load. The composite carrier is prepared by mixing ammonia water, aluminum hydroxide and anhydrous ethanol as a mixed phase, and mixing polystyrene and toluene as an organic phase. The mixed phase and the organic phase are then mixed, and a surfactant is added to perform an oil-water interface reaction. Ammonia water and tetraethyl orthosilicate form a layer of porous silica on the surface of aluminum hydroxide. Then, a layer of sodium hydroxide is coated on the surface of the porous silica to obtain a composite carrier. The load is prepared by mixing the composite carrier and titanium tetrachloride in dichloroethane. Titanium tetrachloride is fixed by the adsorption of titanium tetrachloride by aluminum hydroxide and porous silica and the complexation between polystyrene and titanium tetrachloride, thereby increasing the adsorption amount of titanium tetrachloride. In the reaction, polystyrene complexed with titanium tetrachloride is first brominated. After bromination, the tetrachloride is separated. The titanium tetrachloride is then quickly combined with more polystyrene to continue to be brominated, thereby reducing the reaction time. Aluminum hydroxide can also absorb water to avoid the influence of water in the reaction environment on titanium tetrachloride. The catalyst is prepared by mixing sodium polyacrylate with aluminum chloride, using aluminum chloride as a cross-linking agent to promote the cross-linking of sodium polyacrylate, and then continuing to soak in an aluminum chloride aqueous solution to adsorb a large amount of aluminum chloride to obtain cross-linked particles adsorbing aluminum chloride, i.e., the catalyst. When the catalyst is catalyzing, the aluminum chloride is slowly released to avoid an overly rapid reaction. At the same time, when polystyrene reacts with aluminum chloride on the surface of the cross-linked particles, the reaction heat released can promote the de-crosslinking of the cross-linked particles, thereby also absorbing the reaction heat. The cross-linked particles can also absorb water to avoid the influence of water in the reaction environment on titanium tetrachloride. In the alkali washing after the reaction, the remaining cross-linked particles can further de-crosslink and swell, and then be filtered to remove the catalyst.
[0037] (2) The method for preparing brominated polystyrene of the present invention has good color performance and a yellow index of 11-13;
[0038] (3) The method for preparing brominated polystyrene of the present invention has good thermal stability, with a 1% thermal weight loss temperature of 346-354°C and a 5% thermal weight loss temperature of 377-385°C;
[0039] (4) The method for preparing brominated polystyrene of the present invention has a high bromine content of 68.8-68.9%;
[0040] (5) The method for preparing brominated polystyrene of the present invention has a narrow molecular weight distribution of the prepared brominated polystyrene, with a number average molecular weight Mn of 115,000-121,000 and a molecular weight distribution PD of 1.24-1.27;
[0041] (6) The method for preparing brominated polystyrene of the present invention has good reaction controllability and short reaction time. During the preparation, there is no need to add titanium tetrachloride and aluminum trichloride by dropwise addition, nor is there any need to add titanium tetrachloride and aluminum trichloride separately. DETAILED DESCRIPTION
[0042] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0043] Example 1
[0044] A method for preparing brominated polystyrene, specifically comprising:
[0045] 1. Preparation of main chain bromination inhibitor:
[0046] (1) Preparation of composite carrier: 1L ammonia water, 90g aluminum hydroxide, and 5L anhydrous ethanol were added to a reactor, the temperature of the reactor was controlled to 65°C, the stirring speed was controlled to 200rpm, and the mixture was stirred for 30min to obtain a mixed phase; 2g polystyrene and 0.44L toluene were added to a reactor with a reflux device, the temperature of the reactor was controlled to 111°C, the stirring speed was controlled to 200rpm, and the mixture was stirred and refluxed for 20min, then the mixture was cooled to 40°C, the reflux was stopped, 30g ethyl orthosilicate was added, and the mixture was stirred for 20min. n, obtain an organic phase; add all the above mixed phases to a reactor, control the temperature of the reactor to 65°C, control the stirring speed to 200rpm, then add all the above organic phases to the reactor, add 65g of polyethylene glycol monooctylphenyl ether, continue stirring for 40min, cool naturally to room temperature, stir for 10h, then add to a centrifuge, control the centrifugal speed of the centrifuge to 4000rpm, centrifuge for 10min, take the precipitate, wash the precipitate 3 times with anhydrous ethanol, and dry to obtain a composite carrier;
[0047] The mass concentration of the ammonia water is 20%;
[0048] The D90 particle size of the aluminum hydroxide is 2 μm;
[0049] The number average molecular weight Mn of the polystyrene is 75,000, and the molecular weight distribution PD is 1.2;
[0050] (2) Loading: 100 g of the composite carrier, 20 g of titanium tetrachloride, and 1 L of dichloroethane were added to a reactor, and nitrogen was continuously introduced into the reactor at a rate of 300 mL / min. The stirring speed of the reactor was controlled to 200 rpm, and the reactor was stirred at room temperature for 50 min. The mixture was filtered, the filter residue was collected, and vacuum dried to obtain a main chain bromination inhibitor.
[0051] 2. Preparation of catalyst: Add 14L water to a reactor, control the temperature of the reactor to 40°C, control the stirring speed to 400rpm, slowly add 10g of macromolecular sodium polyacrylate, control the addition speed to 0.8g / min, stir for 10min after the addition is completed, slowly add 9g of small molecule sodium polyacrylate, control the addition speed to 0.7g / min, continue to stir for 2h after the addition is completed, and obtain a sodium polyacrylate aqueous solution; add 1000g of aluminum chloride and 20L of water to a reactor, control the temperature of the reactor to 40°C, control the stirring speed to 400rpm, stir for 10min, dropwise add all of the above sodium polyacrylate aqueous solution, control the dropping time to 50min, continue to stir for 2h after the dropping is completed, naturally cool to room temperature, stand for 30h, filter, take the filter residue, completely immerse it in 0.9L of aluminum chloride aqueous solution, stand for 2h at room temperature, filter, take the filter residue, dry it, and obtain a catalyst;
[0052] The molecular weight of the macromolecular sodium polyacrylate is 3 million;
[0053] The molecular weight of the small molecule sodium polyacrylate is 1 million;
[0054] The mass concentration of the aluminum chloride aqueous solution is 10%;
[0055] 3. Reaction: 100 g polystyrene and 1.5 L dichloroethane were added to a reactor, and nitrogen was continuously introduced into the reactor at a rate of 300 mL / min. After 10 min of introduction, the temperature of the reactor was controlled to 35° C. and the stirring rate was controlled to 200 rpm. The mixture was stirred for 30 min. The temperature of the reactor was controlled to 0° C. 34 g of a main chain bromination inhibitor and 6 g of a catalyst were added, and the mixture was stirred for 20 min. 5.2 L of a dichloroethane solution of N-bromosuccinimide was added dropwise, and the addition time was controlled to 50 min. After the addition was completed, the temperature of the reactor was controlled to room temperature, and the mixture was stirred for 1.5 h. The reaction was terminated. The mixture was washed with a sodium hydroxide aqueous solution for 6 times, with 0.7 L of a sodium hydroxide aqueous solution used for each wash, and washed with water for 3 times, with 0.7 L of water used for each wash, and then filtered. The filtrate was evaporated and crystallized, filtered, and vacuum dried to obtain brominated polystyrene.
[0056] The number average molecular weight Mn of the polystyrene is 75,000, and the molecular weight distribution PD is 1.2;
[0057] The mass concentration of the dichloroethane solution of N-bromosuccinimide is 10%;
[0058] The mass concentration of the sodium hydroxide aqueous solution is 20%.
[0059] Example 2
[0060] A method for preparing brominated polystyrene, specifically comprising:
[0061] 1. Preparation of main chain bromination inhibitor:
[0062] (1) Preparation of composite carrier: 1.1L ammonia water, 95g aluminum hydroxide, and 5.5L anhydrous ethanol were added to a reactor, the temperature of the reactor was controlled to 68°C, the stirring speed was controlled to 250rpm, and the mixture was stirred for 35min to obtain a mixed phase; 2.2g polystyrene and 0.45L toluene were added to a reactor with a reflux device, the temperature of the reactor was controlled to 113°C, the stirring speed was controlled to 250rpm, and the mixture was stirred and refluxed for 25min, then the mixture was cooled to 45°C, the reflux was stopped, 31g ethyl orthosilicate was added, and the mixture was stirred for 2min. 5min to obtain an organic phase; add all the above mixed phases into a reactor, control the temperature of the reactor to 65°C, control the stirring speed to 250rpm, then add all the above organic phases into the reactor, add 68g of polyethylene glycol monooctylphenyl ether, continue stirring for 45min, cool naturally to room temperature, stir for 11h, then add into a centrifuge, control the centrifugal speed of the centrifuge to 4500rpm, centrifuge for 11min, take the precipitate, wash the precipitate 4 times with anhydrous ethanol, and dry to obtain a composite carrier;
[0063] The mass concentration of the ammonia water is 20%;
[0064] The D90 particle size of the aluminum hydroxide is 2 μm;
[0065] The number average molecular weight Mn of the polystyrene is 75,000, and the molecular weight distribution PD is 1.2;
[0066] (2) Loading: 105 g of the composite carrier, 23 g of titanium tetrachloride, and 1.1 L of dichloroethane were added to a reactor, and nitrogen was continuously introduced into the reactor at a rate of 320 mL / min. The stirring speed of the reactor was controlled to 250 rpm, and the mixture was stirred at room temperature for 55 min. The mixture was filtered, the filter residue was collected, and vacuum dried to obtain a main chain bromination inhibitor.
[0067] 2. Preparation of catalyst: Add 14.5L water to a reactor, control the temperature of the reactor to 45°C, control the stirring speed to 450rpm, slowly add 11g of macromolecular sodium polyacrylate, control the addition speed to 0.9g / min, stir for 15min after the addition is completed, slowly add 9.5g of small molecule sodium polyacrylate, control the addition speed to 0.7g / min, continue to stir for 2.5h after the addition is completed, and obtain a sodium polyacrylate aqueous solution; add 1100g of aluminum chloride and 22L of water to a reactor, control the temperature of the reactor to 45°C, control the stirring speed to 450rpm, stir for 15min, dropwise add all of the above sodium polyacrylate aqueous solution, control the dropping time to 55min, continue to stir for 2.5h after the dropping is completed, naturally cool to room temperature, stand for 32h, filter, take the filter residue, completely immerse it in 1L of aluminum chloride aqueous solution, stand for 2.5h at room temperature, filter, take the filter residue, dry it, and obtain a catalyst;
[0068] The molecular weight of the macromolecular sodium polyacrylate is 3 million;
[0069] The molecular weight of the small molecule sodium polyacrylate is 1 million;
[0070] The mass concentration of the aluminum chloride aqueous solution is 10%;
[0071] 3. Reaction: 105g polystyrene and 1.7L dichloroethane were added to a reactor, and nitrogen was continuously introduced into the reactor at a rate of 320mL / min. After 15min of introduction, the temperature of the reactor was controlled to 35°C while the stirring rate was controlled to 250rpm, and the mixture was stirred for 35min. The temperature of the reactor was controlled to 1°C, 34.5g main chain bromination inhibitor and 6g catalyst were added, and the mixture was stirred for 25min. 5.3L dichloroethane solution of N-bromosuccinimide was added dropwise, and the addition time was controlled to 55min. After the addition was completed, the temperature of the reactor was controlled to room temperature, and the mixture was stirred for 1.5h to terminate the reaction. The mixture was washed with sodium hydroxide aqueous solution 6 times, and 0.8L sodium hydroxide aqueous solution was used for each washing. The mixture was washed with water 4 times, and 0.8L water was used for each washing. The mixture was then filtered, and the filtrate was evaporated and crystallized, filtered, and vacuum dried to obtain brominated polystyrene.
[0072] The number average molecular weight Mn of the polystyrene is 75,000, and the molecular weight distribution PD is 1.2;
[0073] The mass concentration of the dichloroethane solution of N-bromosuccinimide is 10%;
[0074] The mass concentration of the sodium hydroxide aqueous solution is 20%.
[0075] Example 3
[0076] A method for preparing brominated polystyrene, specifically comprising:
[0077] 1. Preparation of main chain bromination inhibitor:
[0078] (1) Preparation of composite carrier: 1.1L ammonia water, 100g aluminum hydroxide and 6L anhydrous ethanol were added to a reactor, the temperature of the reactor was controlled to 70°C, the stirring speed was controlled to 300rpm, and the mixture was stirred for 40min to obtain a mixed phase; 2.3g polystyrene and 0.46L toluene were added to a reactor with a reflux device, the temperature of the reactor was controlled to 113°C, the stirring speed was controlled to 300rpm, and the mixture was stirred and refluxed for 30min, then the mixture was cooled to 50°C, the reflux was stopped, 32g ethyl orthosilicate was added, and the mixture was stirred for 3min. 0min to obtain an organic phase; add all the above mixed phases into a reactor, control the temperature of the reactor to 70°C, control the stirring speed to 300rpm, then add all the above organic phases into the reactor, add 70g of polyethylene glycol monooctylphenyl ether, continue stirring for 50min, cool naturally to room temperature, stir for 12h, then add into a centrifuge, control the centrifugal speed of the centrifuge to 5000rpm, centrifuge for 12min, take the precipitate, wash the precipitate 5 times with anhydrous ethanol, and dry to obtain a composite carrier;
[0079] The mass concentration of the ammonia water is 20%;
[0080] The D90 particle size of the aluminum hydroxide is 2 μm;
[0081] The number average molecular weight Mn of the polystyrene is 75,000, and the molecular weight distribution PD is 1.2;
[0082] (2) Loading: 110 g of the composite carrier, 25 g of titanium tetrachloride, and 1.2 L of dichloroethane were added to a reactor, and nitrogen was continuously introduced into the reactor at a rate of 350 mL / min. The stirring speed of the reactor was controlled to 300 rpm, and the mixture was stirred at room temperature for 60 min. The mixture was filtered, the filter residue was collected, and vacuum dried to obtain a main chain bromination inhibitor.
[0083] 2. Preparation of catalyst: add 15L water to the reactor, control the temperature of the reactor to 50°C, control the stirring speed to 500rpm, slowly add 12g of macromolecular sodium polyacrylate, control the addition speed to 1g / min, stir for 20min after the addition is completed, slowly add 10g of small molecule sodium polyacrylate, control the addition speed to 0.8g / min, continue to stir for 2.5h after the addition is completed, and obtain a sodium polyacrylate aqueous solution; add 1200g of aluminum chloride and 23L of water to the reactor, control the temperature of the reactor to 50°C, control the stirring speed to 500rpm, stir for 20min, drip all the above sodium polyacrylate aqueous solution, control the dripping time to 60min, continue to stir for 3h after the dripping is completed, naturally cool to room temperature, stand for 35h, filter, take the filter residue, completely immerse it in 1L of aluminum chloride aqueous solution, stand for 3h at room temperature, filter, take the filter residue, dry it, and obtain the catalyst;
[0084] The molecular weight of the macromolecular sodium polyacrylate is 3 million;
[0085] The molecular weight of the small molecule sodium polyacrylate is 1 million;
[0086] The mass concentration of the aluminum chloride aqueous solution is 10%;
[0087] 3. Reaction: 110 g of polystyrene and 1.8 L of dichloroethane were added to a reactor, and nitrogen was continuously introduced into the reactor at a rate of 350 mL / min. After 20 min of introduction, the temperature of the reactor was controlled to 40° C. and the stirring rate was controlled to 300 rpm. The mixture was stirred for 40 min. The temperature of the reactor was controlled to 2° C. 35 g of a main chain bromination inhibitor and 6.2 g of a catalyst were added, and the mixture was stirred for 30 min. 5.4 L of a dichloroethane solution of N-bromosuccinimide was added dropwise, and the addition time was controlled to 60 min. After the addition was completed, the temperature of the reactor was controlled to room temperature, and the mixture was stirred for 1.5 h. The reaction was terminated. The mixture was washed with a sodium hydroxide aqueous solution for 7 times, using 0.8 L of a sodium hydroxide aqueous solution for each wash, and washed with water for 4 times, using 0.8 L of water for each wash, and then filtered. The filtrate was evaporated and crystallized, filtered, and vacuum dried to obtain brominated polystyrene.
[0088] The number average molecular weight Mn of the polystyrene is 75,000, and the molecular weight distribution PD is 1.2;
[0089] The mass concentration of the dichloroethane solution of N-bromosuccinimide is 10%;
[0090] The mass concentration of the sodium hydroxide aqueous solution is 20%.
[0091] Comparative Example 1
[0092] The technical scheme is changed on the basis of the preparation method of brominated polystyrene in Example 2. The specific changes are as follows: in the step of preparing the main chain bromination inhibitor in step 1, the step of preparing the composite carrier in step (1) is omitted, and in the loading step in step (2), aluminum hydroxide with a D90 particle size of 2 μm is used in place of the composite carrier.
[0093] Comparative Example 2
[0094] The technical scheme is changed on the basis of the preparation method of brominated polystyrene in Example 2. The specific changes are: omitting the second step of preparing the catalyst, and using 2g of aluminum chloride instead of 6g of the catalyst in the third reaction step.
[0095] Test Case
[0096] The yellowness index, 1% thermal weight loss temperature, 5% thermal weight loss temperature, bromine content, number average molecular weight Mn, and molecular weight distribution PD of the brominated polystyrene prepared in Examples 1-3 and Comparative Examples 1-2 were tested, and the test results are as follows:
[0097]
[0098] It can be seen from the results of the test examples that by first preparing a composite carrier in the step of preparing the main chain bromination inhibitor and using the composite carrier to load titanium tetrachloride, the yellowness index and molecular weight distribution PD of the prepared brominated polystyrene can be reduced, and the 1% thermal weight loss temperature, 5% thermal weight loss temperature and bromine content of the prepared brominated polystyrene can also be increased.
[0099] Unless otherwise specified, all percentages used in the present invention are by mass.
[0100] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing brominated polystyrene, characterized in that: include: Preparation of main chain bromination inhibitor, preparation of catalyst, reaction; The method for preparing the main chain bromination inhibitor comprises: preparing a composite carrier, loading; The composite carrier is prepared by mixing ammonia water, aluminum hydroxide and anhydrous ethanol, stirring at 65-70° C. to obtain a mixed phase; mixing polystyrene and toluene, stirring and refluxing at 111-113° C., cooling to 40-50° C., adding tetraethyl orthosilicate, stirring to obtain an organic phase; stirring the mixed phase at 65-70° C., then adding the organic phase and polyethylene glycol monooctylphenyl ether, continuing to stir, cooling to room temperature, stirring, centrifuging, taking a precipitate, washing and drying to obtain a composite carrier; The support is prepared by mixing the composite support, titanium tetrachloride and ethylene dichloride, stirring at room temperature under the protection of nitrogen, filtering, taking the filter residue, and vacuum drying to obtain a main chain bromination inhibitor; The catalyst preparation comprises the following steps: stirring the first portion of water at 40-50° C., adding a large molecular sodium polyacrylate, stirring after the addition is completed, adding a small molecular sodium polyacrylate, and continuing to stir after the addition is completed to obtain a sodium polyacrylate aqueous solution; mixing aluminum chloride and the second portion of water, stirring at 40-50° C., dripping the sodium polyacrylate aqueous solution, continuing to stir after the dripping is completed, cooling to room temperature, standing, filtering, taking a filter residue, completely immersing it in an aluminum chloride aqueous solution, standing at room temperature, filtering, taking a filter residue, and drying to obtain a catalyst; In the catalyst preparation, the molecular weight of the macromolecular sodium polyacrylate is 3 million; The molecular weight of the small molecule sodium polyacrylate is 1 million; In the reaction, polystyrene and dichloroethane are mixed, stirred at 35-40°C for 30-40 minutes under the protection of nitrogen, then cooled to 0-2°C, main chain bromination inhibitor and catalyst are added, stirred for 20-30 minutes, and a dichloroethane solution of N-bromosuccinimide is added dropwise. After the addition is completed, the mixture is stirred at room temperature for 1.5 hours to terminate the reaction, washed with sodium hydroxide aqueous solution, washed with water, and then filtered. The filtrate is evaporated and crystallized, filtered, and vacuum dried to obtain brominated polystyrene.
2. The method for preparing brominated polystyrene according to claim 1, characterized in that: In the preparation of the composite carrier, the usage ratio of ammonia water, aluminum hydroxide, anhydrous ethanol, polystyrene, toluene, tetraethyl orthosilicate and polyethylene glycol monooctylphenyl ether is 1-1.1L:90-100g:5-6L:2-2.3g:0.44-0.46L:30-32g:65-70g.
3. The method for preparing brominated polystyrene according to claim 1, characterized in that: In the preparation of the composite carrier, the mass concentration of the ammonia water is 20%; The D90 particle size of the aluminum hydroxide is 2 μm; The number average molecular weight Mn of the polystyrene is 75,000, and the molecular weight distribution PD is 1.
2.
4. The method for preparing brominated polystyrene according to claim 1, characterized in that: In the loading, the usage ratio of the composite carrier, titanium tetrachloride and ethylene dichloride is 100-110 g:20-25 g:1-1.2 L.
5. The method for preparing brominated polystyrene according to claim 1, characterized in that: In the preparation of the catalyst, the usage ratio of the first portion of water, macromolecular sodium polyacrylate, small molecule sodium polyacrylate, aluminum chloride, the second portion of water, and aluminum chloride aqueous solution is 14-15L:10-12g:9-10g:1000-1200g:20-23L:0.9-1L.
6. The method for preparing brominated polystyrene according to claim 1, characterized in that: In the catalyst preparation, the mass concentration of the aluminum chloride aqueous solution is 10%; The addition rate of the macromolecular sodium polyacrylate is 0.8-1 g / min; The addition rate of the small molecule sodium polyacrylate is 0.7-0.8 g / min; The dropping time of the sodium polyacrylate aqueous solution is 50-60 minutes.
7. The method for preparing brominated polystyrene according to claim 1, characterized in that: In the reaction, the usage ratio of polystyrene, ethylene dichloride, main chain bromination inhibitor, catalyst, and ethylene dichloride solution of N-bromosuccinimide is 100-110 g: 1.5-1.8 L: 34-35 g: 6-6.2 g: 5.2-5.4 L.
8. The method for preparing brominated polystyrene according to claim 1, characterized in that: In the reaction, the number average molecular weight Mn of the polystyrene is 75,000, and the molecular weight distribution PD is 1.2; The mass concentration of the dichloroethane solution of N-bromosuccinimide is 10%; The mass concentration of the sodium hydroxide aqueous solution is 20%; The dropwise addition time of the dichloroethane solution of N-bromosuccinimide is 50-60 minutes.
Citation Information
Patent Citations
Method for continuously preparing brominated polystyrene
CN117106109A
Synthesis method of brominated polystyrene with high thermal stability
CN117247482A
Cited By
Brominated polystyrene with high thermal stability and preparation method thereof
CN121779836A